IP telephony demystified - Camp, Ken (New York : McGraw Hill Education, 2003)
This handbook is designed to demystify IP telephony for business people and technology generalists. It discusses: IP protocol breakdown -SIP, H.323, Megaco/H.248; quality of service - IntServ, DiffServ, and MPLS; integrating voice into a LAN data environment; and cost and service implications.
Chapter 1: History and Overview of Telecommunications -- Chapter 2: The Internet and IP Networking -- Chapter 3: Fundamentals of Packetized Voice -- Chapter 4: IP Telephony Protocols -- Chapter 5: The Lure of IP Telephony: Can It Work For Me? -- Chapter 6: Performance, Quality of Service, and Traffic Engineering -- Chapter 7: Gateways Between Networks -- Chapter 8: Premise-Based Telephony -- Chapter 9: Network-Based IP Telephony Services -- Chapter 10: The Future of IP Telephony --
Includes index.
Keywords: INTERNET TELEPHONY